ANALISIS YURIDIS PENYELESAIAN SENGKETA KEPALA DESA YANG MENDAPAT SUARA SAMA DI DESA MASBAGIK SELATAN KABUPATEN LOMBOK TIMUR - HULAIMI (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
The purpose of this research is to find out how the dispute resolution mechanism of the election results for the Head of South Masbagik Village, East Lombok Regency is based on the Laws and Regulations. Knowing how the legal considerations in Decision Number: 08 / G / 2018 / PTUN.Mtr and PTUN Surabaya Decision Number: 173 / B / 2018 / PT.TUN.SBY are in accordance with statutory regulations in resolving the same vote dispute. This study the authors use the Normative research method, with an approach method using library legal materials in other words, library research (Library Reaserch). This study the authors used a normative research method, with an approach method using library law materials, in other words, library research (Library Reaserch). The method of collecting legal materials used is documentation study, namely by recording information from legal materials related to dispute resolution mechanisms based on statutory regulations, as well as those obtained from other sources, either expert opinion, research results or journals.